Proceedings of the 2014 Workshop on Mobile Augmented Reality and Robotic Technology-Based Systems 2014
DOI: 10.1145/2609829.2609836
|View full text |Cite
|
Sign up to set email alerts
|

Robotics enabled in-home environment screening for fall risks

Abstract: Fall risks present in living environment are the leading cause of mortality in older adults. Falling on the floor may cause great harm to older people living alone, which in many cases goes unnoticed for several days until the symptoms become severe. Limited number of trained professionals to assess a house for fall risks and higher costs make the prevention of fall risks inaccessible to many necessitous patients. Removing these potential risk factors can provide older adults a safer living condition for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In these studies, patients perform physical activities and cognitively demanding tasks to determine fall risks. Du et al [ 64 ] developed a robotic system that screens the subjects’ home, for environmental fall hazards. This system is operated remotely by clinicians, to automate home assessments that are typically conducted by in-person visits.…”
Section: Fall Prevention Systemsmentioning
confidence: 99%
“…In these studies, patients perform physical activities and cognitively demanding tasks to determine fall risks. Du et al [ 64 ] developed a robotic system that screens the subjects’ home, for environmental fall hazards. This system is operated remotely by clinicians, to automate home assessments that are typically conducted by in-person visits.…”
Section: Fall Prevention Systemsmentioning
confidence: 99%
“…Technology may advance this further. For example, a relatively new innovation includes a robot control system for in-home environment screening of falls hazards [7]. This system enables a health professional to assess a house remotely and to interact with the user using telepresence.…”
Section: Introductionmentioning
confidence: 99%
“…Where extrinsic factors are considered, many apps still require a clinician’s input to provide advice or interpret results. For example, Hamm et al (2019) reported an app that allowed carers to conduct assessments for assistive technologies to improve home safety, and two papers described the use of technology to allow clinicians to remotely conduct safety and hazard assessments via video (Romero et al , 2018) and robotic technology (Du et al , 2014). Whilst these papers reported good usability and acceptability from participants, these apps still require the involvement of a clinician, which leaves such services out of reach for those who do not meet the relevant support, service criteria.…”
Section: Introductionmentioning
confidence: 99%